Load Capacity Comparison of Different Wet Multi-Plate Clutches with Sinter Friction Lining with Regard to Spontaneous Damage Behavior - Schneider, Thomas; Bedrikow, Alexandre Beiderwellen; Völkel, Katharina; Pflaum, Hermann; Stahl, Karsten (Tribology in Industry, 2022)
Wet multi-plate clutches are safety-critical components of drive trains. Failure and damage must therefore be strongly avoided. In contrast to long-term damage, spontaneous damage and failures are difficult to predict. Different authors have already theorized the influence of different parameters on the carrying capacity. This paper extends the analysis of these effects by conducting experimental investigations. Furthermore, an evaluation method that allows to compare different clutch systems regarding their load carrying capacity is presented. Clutch systems with variation of oil flow, plate thickness, coating and groove pattern were tested, and their results analyzed. Statistical methods were used to consider the variance of the measurements. Lastly, recommendations are formulated for the development of clutch systems concerning the load carrying capacity. Strong trends can be seen for the influences of the thickness of the steel plate and oil flow rate, but these can only be statistically substantiated for the variation of the oil flow rate. For the variation of the coating and the grooving, only slight to no differences are discernible.
CRIS-Team Scopus Importer:2025-05-19
Keywords: Damage behavior; Load capacity of clutches; Multiple plate clutch; Scuffing; Sinter friction lining; Spontaneous damage; Wet friction clutch